2022
DOI: 10.22541/au.164040480.07315088/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interdependencies of cellular and humoral immune responses in heterologous and homologous SARS‑CoV‑2 vaccination

Abstract: Background: Homologous and heterologous SARS-CoV-2 vaccinations yield different spike protein-directed humoral and cellular immune responses. This study aimed to explore their currently unknown interdependencies. Methods: COV-ADAPT is a prospective, observational cohort study of 417 healthcare workers who received vaccination with homologous ChAdOx1 nCoV-19, homologous BNT162b2 or with heterologous ChAdOx1 nCoV-19/BNT162b2. We assessed humoral (anti-spike-RBD-IgG, neutralizing antibodies, avidity) and cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Moreover, both ChAd and BNT vaccines could generate interferon. Even though previous studies found that there was no difference of the effect of generation of interferon between adenovirus vaccine and the mRNA vaccine three weeks after the first dose [28] , and 2-12 weeks following secondary dose [29] , the differences in interferon production between adenovirus vaccine and the mRNA vaccine within one week remain unknown, which may be another possible biologic reason for the results we found. Future studies are needed to understand the potential mechanisms.…”
Section: Discussioncontrasting
confidence: 65%
“…Moreover, both ChAd and BNT vaccines could generate interferon. Even though previous studies found that there was no difference of the effect of generation of interferon between adenovirus vaccine and the mRNA vaccine three weeks after the first dose [28] , and 2-12 weeks following secondary dose [29] , the differences in interferon production between adenovirus vaccine and the mRNA vaccine within one week remain unknown, which may be another possible biologic reason for the results we found. Future studies are needed to understand the potential mechanisms.…”
Section: Discussioncontrasting
confidence: 65%